JEJAK GERAKAN DI /TII KAHAR MUZAKKAR DALAM INGATAN MASYARAKAT BULUKUMBA DAN SINJAI - Asrini; Rhabjel Aulii Idham Baso; Saslim; Riska Cahyani; Rahmat Hidayat (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to trace the legacy of the DI/TII movement led by Kahar Muzakkar, which remains embedded in the collective memory of the communities in Bulukumba and Sinjai Regencies, South Sulawesi. By adopting an oral history approach and a study of collective memory, this research explores how local communities remember, interpret, and pass down narratives about this armed movement from one generation to the next. Data was collected through in-depth interviews with historical actors, eyewitnesses, and their descendants, and supported by relevant archives and literature. The research findings reveal that the community’s memories of the DI/TII are fragmented between experiences of trauma and narratives of heroism; some communities view this movement as a dignified ideological struggle, while others see it as a source of suffering and fear. These results affirm that the construction of memory is not merely a record of past events, but a social process that is continuously reproduced in accordance with group interests and identities. This research makes an important contribution to deepening our understanding of the legacy of armed conflict in the social and cultural life of the people of South Sulawesi.